Forensic Examination of Counterfeit New Turkish Lira Bimetallic Coins - CAKIR, ISMAIL; BULENT UNER, H. (Asian Journal of Chemistry, 2010)
In this study, total 200 (100 genuine and 100 counterfeit) coins (1 YTL) were quantitatively analyzed by scanning electron microscope with energy dispersive X-ray spectrometer (SEM/EDS) after determinations of their diameter, thickness, weight and appearance. The weight of each One New Turkish Lira (both genuine and counterfeit coins) was measured to sub-milligram using an electronic balance. The diameter and rim thickness of each One New Turkish Lira (both genuine and counterfeit coins) was measured twice employing a vernier caliper. SEM/ EDS is a widely used nondestructive elemental analysis method. SEM sample stub using double-sided carbon adhesive tape. The samples were then subjected to morphological observation and elemental analysis via SEM/EDS without any coating. The working distance and magnification powers were varied while secondary image observation. A fixed working distance of 15 mm and 200 times magnification were employed during energy dispersive X-ray analysis. The major elements detected in the outer ring of both genuine and counterfeit coins were Cu, Ni and Zn while the elements detected in the inner disc of genuine and counterfeit coins were also Cu, Ni and Zn. The major elements percentage detected in the genuine coins were Cu, Ni and Zn which were significantly different from the counterfeit coin samples. Present work demonstrates, therefore, the possibility of discriminating genuine and counterfeit coins using SEM/EDS, by means of a relatively rapid and effective method.